Near-Field Periodic Subwavelength Holey Metallic Plate for Far-Field Superresolution Focusing - Xiao-Hua Wang; Min Hu; Bing-Zhong Wang; Gang Zheng; Peng Chen (IEEE Photonics Journal)
Far-field focusing with superresolution aided by a proposed metallic plate is investigated in this paper. The proposed near-field structure can be employed to distinguish point-like sources with subwavelength distance and enhance the field strength based on the spoof surface plasmon polaritons theory, and by the simulations of near- and far-field spectrums, it can be found that some near-field evanescent waves carried the superresolution information can be converted to propagation waves and propagate to the far-field. Therefore, with the help of time reversal imaging process, the far-field superresolution focusing is validated by the experiments in laboratory environment. A resolution of $\sim$ $λ$ /13 is achieved from the last results, which is well beyond the diffraction limit.